KAJIAN AKADEMIK TENTANG PEMOTONGAN GAJI PEGAWAI NEGERI SIPIL YANG SEDANG MENEMPUH TUGAS BELAJAR DI LINGKUNGAN KEMENTERIAN PENDIDIKAN NASIONAL DALAM SISTEM KEUANGAN NEGARA - Indrawati Indrawati; Rr. Herini Siti Aisyah (Universitas Airlangga, 2010)
There are many various efforts have been taken by the Government to improve the quality of education in Indonesia, one of them with empowerment and improving the quality of teachers and lecturers as professional educators must have the academic qualifications, competence, education certificates, and have the ability to achieve national education goals. However, as consequences Government cut the student salaries component included basic salary and allowances, and only receive the benefits of the family. The existing laws concerning the financial management of state budget allocations, especially civil servants salaries that are taking education in the Ministry of National Education in Indonesia that are incompatible with the principles of good governance. While the principle of state financial accountability contained in Article 23 art (1) of UUD 1945 that is